The Effectiveness of Non-invasive Complementary Therapies in Reducing Postoperative Nausea and Vomiting Following Abdominal Laparoscopic Surgery in Women: A Systematic Review - Hewitt, Vivien; Watts, Robin (University of Adelaide, 2009)
Objectives - The objective of this review was to determine from the available evidence the most effective non-invasive complementary therapies for reducing the incidence and/or severity of postoperative nausea and vomiting in women undergoing abdominal laparoscopies.